Measuring the complexity of treatment for challenging behavior using the treatment intensity rating form. (2nd July 2016) - Zarcone, Jennifer R.; Hagopian, Louis; Ninci, Jennifer; McKay, Chloe; Bonner, Andrew; Dillon, Christopher; Hausman, Nicole
Abstract : Objectives : The goal of this study was to develop and evaluate a tool to measure the complexity and intensity of psychotropic medication interventions, behavioral interventions, and issues related to crisis management for challenging behavior using a standardized rating form. Method : The Treatment Intensity Rating Form (TIRF) is a 10-item scale with three categories: pharmacological interventions, behavior supports, and protective equipment. In a retrospective review, we examined the final treatment recommendations for 74 individuals with self-injurious behavior (SIB) based on psychiatric and behavioral notes and reports. We also compared whether TIRF scores differed across individuals for whom SIB was maintained by social reinforcement (e.g. to access attention or toys/activities, or escape from tasks) vs. those for whom SIB was maintained by automatic reinforcement (e.g. occurs independent of social variables, and is presumed to be maintained by sensory reinforcement). Results : The TIRF was demonstrated to have strong inter-rater reliability (98%) and appears to have good face validity. As hypothesized, individuals with SIB maintained by automatic reinforcement had significantly more medication trials ( p =0.0005) and required more protective equipment than individuals with SIB maintained by social reinforcement ( p =0.0002). Antidepressant medication was used more often with individuals with automatically reinforced SIB, although antipsychotics and anticonvulsants were also commonly used across both groups. Conclusion : Findings provide initial support for the TIRF's reliability and face validity as a measure of the level of complexity of medical and behavioral treatment plans — although additional research is needed to fully evaluate its psychometric properties.